Shadow dispersion of PV Array under variable irradiance for superior power Generation by Magic Square Configuration - Sreenivasa Reddy, G; Bramhananda Reddy, T; Vijaya Kumar, M (International Journal of Engineering and Technology, 2018)
The PV array generates smaller amount of the power compared with other electrical power generation components. There are many components that are adversely effected the output of PV array in such components, one is partial shading. Due to this, each module in PV array receives different solar irradiations causes different P-V characteristics of its peak values. This paper presents a pioneering method called as Magic Square configuration has been proposed to enhance the generated power of photovoltaic modules by configuring those are under affect of shade. Thus there is no change of electrical arrangement of PV modules in an array but only the objective location in the total cross tied (TCT) array is rearranged according to the magic square arrangement. Proposed paper gives comparison data with the conventional configuration method and hence the performance is calculated. The proposed technique provides a better solution that how shadow effect on the PVÂ modules has been reduced and how this shadow is distributed, and not only that also gives an ideaÂ about how the inequality losses due to the partial shading is effectively reduced. The power loss of Â various configurations of 3X3 and 4X4 array has been compared. The proposed technique is validated through MATLAB/Simulink environment.Â